F.r.t.l. Jeanne Humbert (Jeanne Rigaudin), Humbert, Eugénie de Bast (?) before the head office of Génération Consciente (1909)
F.r.t.l. Jeanne Humbert (Jeanne Rigaudin), Humbert, Eugénie de Bast (?) before the head office of Génération Consciente.